New Insights of Infiltration Process of Argyrodite Li6PS5Cl Solid Electrolyte into Conventional Lithium-Ion Electrodes for Solid-State Batteries - Artur Tron; Andrea Paolella; Alexander Beutl (Batteries, 2023)
All-solid-state lithium-ion batteries based on solid electrolytes are attractive for electric applications due to their potential high energy density and safety. The sulfide solid electrolyte (e.g., argyrodite) shows a high ionic conductivity (10−3 S cm−1). There is an open question related to the sulfide electrode’s fabrication by simply infiltrating methods applied for conventional lithium-ion battery electrodes via homogeneous solid electrolyte solutions, the structure of electrolytes after drying, chemical stability of binders and electrolyte, the surface morphology of electrolyte, and the deepening of the infiltrated electrolyte into the active materials to provide better contact between the active material and electrolyte and favorable lithium ionic conduction. However, due to the high reactivity of sulfide-based solid electrolytes, unwanted side reactions between sulfide electrolytes and polar solvents may occur. In this work, we explore the chemical and electrochemical properties of the argyrodite-based film produced by infiltration mode by combining electrochemical and structural characterizations.